Visual Video Media in Improving Poetry Writing Skills of Students of SDN Babussalam 5 West Lombok - Muhazzab, Muhazzab; Triyono, Triyono; Kholid, Kholid; Setiyadi, DB Putut; Hersulastuti, Hersulastuti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the improvement of learning activities and poetry writing skills, as well as the response to the use of audiovisual media by fifth-grade students of State Elementary School 5 Babussalam. The research method uses a quantitative approach. Data collection was carried out through observation, documentation, tests, and non-tests through two cycles. The data collection techniques used tests and non-tests, with written tests and non-tests using observation sheets and documentation from teachers and students, as well as questionnaires. Data analysis techniques were carried out using descriptive analysis. The results of this study, in the form of student activity in the Pre-cycle was 68%, increased in cycle I to 80.50% and continued to increase to 88% in cycle II. Teacher activity in an effort to improve students' poetry writing in the Pre-cycle was 72.50% and increased to 86.50% in cycle I and increased significantly in Cycle II to 91.25%. And the completeness of student learning in writing poetry in the pre-cycle was 3.13%, increased to 21.88% in cycle I and increased further to 87.10% in cycle II. The students' responses were 84% with the category of strongly agree or very positive. Therefore, it can be concluded that the use of audio-visual media can improve students' learning activities and poetry writing skills and the responses were very positive for fifth grade students of Elementary School 5 Babussalam.